The Effect of Adenotonsillectomy on Children's Behavior and Cognitive Performance with Obstructive Sleep Apnea Syndrome: State of the Art - Paola Di Mauro; Salvatore Cocuzza; Antonino Maniaci; Salvatore Ferlito; Deborak Rasà; Roberta Anzivino; Claudio Vicini; Giannicola Iannella; Ignazio La Mantia (MDPI AG, 2021)
(1) Background: This systematic review was designed to analyze adenotonsillectomy's role in treating behavioural disorders and sleep-related quality of life in pediatric OSAS. (2) Methods: Papers that report pre-operative and post-operative outcomes by using the Epworth sleepiness scale, OSA-18, NEPSY, Conners' rating scale, BRIEF, PSQ-SRBD, PedsQL and CBCL. We performed a comprehensive review of English papers published during the last 20 years regarding behavioural disorders in OSAS patients and adenotonsillectomy. (3) Results: We included 11 studies reporting behavioral outcomes and sleep related quality of life after surgery. We investigated changes in behavior and cognitive outcomes after AT, and we found significant improvements of the scores post-AT in almost all studies. After comparing the AT group and control group, only one study had no difference that reached significance at one year post-AT. In another study, it did not show any significant improvement in terms of all behavioural and cognitive outcomes. The questionnaires on sleep-related quality of life after AT (PSQ-SRBD or ESS or OSA-18 or KOSA) may improve with positive changes in sleep parameters (AHI, ODI and SpO2). Furthermore, there is a significantly higher decrease in OSAS symptoms than the pre-AT baseline score. (4) Conclusion: Future studies should pay more attention to characterizing patient populations as well as rapid surgical treatments through existing criteria.